Design Support System for Parabolic Trough Solar Collector - Woldemichael, Dereje; Woldeyohannes, Abraham; Lim, Chye (Asian Network for Scientific Information, 2012)
Parabolic Trough Collector (PTC) is special kind of heat exchanger that is able to transfer solar radiation energy to fluid medium that flow through it. Designing a PTC for a specific working condition requires determination of several parameters and referring to a number of design standards and handbooks. Hence, a design support system is required to determine the necessary parameters and simulate different working conditions. Although, a number of design support systems for solar collectors are available in the market, they are either expensive or limited to certain types of solar collectors. This study presents an in-house design simulation software for parabolic trough collector. The simulation software was coded in Microsoft Visual Studio.Net 2010. Through its Graphical User Interface (GUI), the software allows the user to give input parameters, explore built in standards and review outputs. The output parameters include geometric design parameters, heat losses coefficient and efficiencies. The output parameters are important in the initial stage of designing parabolic trough collectors to reduce design time and effort. The results of the simulation software are validated with published experimental and analytical results.